90-Day Complications Following the Distal Tibia Allograft Procedure. Issue 7 (30th July 2018) - Frank, Rachel M.; Richardson, Catherine; Gregory, Bonnie; Sumner, Shelby; O'Brien, Michael C.; Bernardoni, Emon; Verma, Nikhil N.; Cole, Brian J.; Nicholson, Gregory P.; Provencher, Matthew T.; Romeo, Anthony A.
Objectives: To describe complications occurring within 90-days following the distal tibia allograft (DTA) procedure. Methods: Consecutive patients undergoing DTA for anterior glenohumeral instability by fellowship-trained surgeons were included for analysis. Indications for DTA included primary or recurrent anterior instability with clinically significant anterior glenoid bone loss, failed prior arthroscopic stabilization, and/or failed prior Latarjet. All complications that occurred within 90-days of surgery were analyzed and correlated with demographic factors. Results: A total of 63 consecutive patients (average age 26.4±8.2 years, 90% male) were included. Fifty patients (79%) had undergone prior ipsilateral shoulder surgery, including 8 undergoing prior Latarjet (13%). The average glenoid bone loss prior to DTA was 29±7%. There were 5 total complications within 90 days of surgery, for an overall short-term complication rate of 7.9%. The 58 patients without complications had an average age of 26.2±7.9 years (95% male), with 45 (78%) having had prior shoulder surgery. Three of these 5 required subsequent surgery, including 1 revision DTA for hardware failure, 1 subscapularis repair, and 1 debridement for retained foreign body. The remaining 2 complications were transient and resolved with non-operative treatment, including 1 patient with postoperative pain requiring a subacromial injection, and 1 patient with a stitch abscess treated with oral antibiotics. The 5 patients experiencing complications had an average age of 29.0±11.5 years (40% male), with all 5 (100%) having had prior shoulder surgery. There were no episodes of recurrent instability. Conclusion: The overall 90-day complication rate following DTA is 7.9%, substantially lower than the previously described rate of 25% in patients undergoing Latarjet, despite the majority of patients having had at least 1 prior ipsilateral shoulder surgery. This information can be used to counsel patients on the risks of early complications following DTA.